Power Relationships in Two Web-based Courses - John M. Pettitt (Adult Education Research Conference, 2002)
This study examined the experiences of ten adult distance learners enrolled in on-line undergraduate business management courses. The frameworks of Rogers and Giddens have relevance for these distance learners who displayed strategies for exerting agency over time, proximity, and authority in order to maintain, obtain, surrender, or share control.